Along which identity lines does 21st century Britain divide? Evidence from Big Brother - Lane, Tom (SAGE Publications, 2020)
This paper measures discrimination in the reality TV show Big Brother, a high-stakes environment. Data on contestants’ nominations are taken from 35 series of the British version of the show, covering the years 2000-2016. Race and age discrimination are found, with contestants more likely to nominate those of a different race and those different in age from themselves. However, no discrimination is identified on the basis of gender, geographical region of origin, or level of education. Racial discrimination is driven by males, but females exhibit stronger age discrimination than males. Age discrimination is driven by the younger contestants discriminating against the older. Regional differences emerge, particularly between contestants from Greater London and those from the north of England; northerners have a stronger tendency to engage in racial and age discrimination, and to discriminate in favour of the opposite gender.